Effectiveness of movement representation techniques in non-specific shoulder pain: a systematic review and meta-analysis - Nuray Alaca; Ali Ömer Acar; Sergen Öztürk (Scientific Reports)
Abstract This systematic review and meta-analysis aims to assess the effects of movement representation techniques (MRT) on pain, range of motion, functional outcomes, and pain-related fear in patients with non-specific shoulder pain (NSSP). A literature search conducted in PubMed, PEDro, EBSCO, Scopus, Cochrane Library, ScienceDirect, and gray literature on April 31, 2023. We selected seven randomized controlled trials based on the PICOS framework. Incomplete data or non-NSSP excluded. Study quality was assessed using the PEDro scale (mean score = 6.43), and certainty of evidence was evaluated with the GRADE approach. MRT demonstrated a large effect size for pain reduction (high heterogeneity, I2 = 85.2%, Hedges’g = 1.324, 95% CI = 0.388–2.260, P = 0.006), functional improvement (moderate heterogeneity, I2 = 70.82%, Hedges’g = 1.263, 95% CI = 0.622–1.904, P < 0.001), and reduction of pain-related fear (moderate heterogeneity, I2 = 70.86%, Hedges’g = 0.968, 95% CI = 0.221–1.716, P < 0.001). MRT also showed significant benefits for range of motion, particularly in flexion (low heterogeneity, I2 = 26.38%, Hedges’g = 0.683), abduction (low heterogeneity, I2 = 33.27%, Hedges’g = 0.756), and external rotation (low heterogeneity, I2 = 48.33%, Hedges’g = 0.542) (P < 0.001 for all), while no significant effect was found for internal rotation (P > 0.05). No publication bias was detected. While limited evidence and methodological concerns necessitate further research, MRT appears to positively impact pain, range of motion, functional outcomes, and pain-related fear in NSSP patients.